FACTORS ASSOCIATED WITH THE NUTRITIONAL STATUS IN TODDLERS IN PUBLIC HEALTH CENTER LUBUK KILANGAN - okta vianis (HUMAN CARE JOURNAL, 2016)
Based on monitoring reports nutritional status of children in Lubuk Kilangan Puskesmas Padang in 2014, from 291 infants who weighed by BB / U, known malnutrition by 10 people (3.44%), malnutrition as many as 54 people (18.56%), and good nutrition as much as 222 (76.3%). The purpose of this study to see if Factors Associated with the Nutritional Status In Toddlers in Sub Bandar Buat Padang District of Lubuk Kilangan 2016.Types and methods of this research is analytic survey with cross sectional design. The research was conducted in the village of Lubuk Kilangan Bandar Buat District of Padang in May 2016. The population is all the mothers who have children amounted to 755 people. Samples taken as many as 88 people with cluster random sampling techniques and sample used for the randomization Simple Random Sampling technique. Data collected by using a questionnaire. Processing of data by univariate and bivariate data analysis performed using Chi-Square test.The results were obtained over the majority 51.1% children have malnutrition. Mothers who are knowledgeable low of 3.6%, which the family income <1.615 million as much as 47.7%. Mothers who do not give exclusive breastfeeding much as 52.3%. Of test statistics in get a significant relationship between the nutritional status of children with a mother knowledge (p value 0.000), there was a significant relationship between the nutritional status of children with family incomes (p value 0.000), and no significant correlation between the nutritional status of children with exclusive breastfeeding ( p value 0.034). It was concluded that there is a relationship between the nutritional status of children with the knowledge of the mother, family income and exclusive breastfeeding in Lubuk Kilangan Puskesmas Padang Year 2016. For the Lubuk Kilangan health center in order to do counseling at least 1 time a month on Nutrition in infants in order to improve knowledge of mothers on nutritional status.